Acharya Jagadish Chandra Bose: His Life and Work (1858-1937) - KOTHARI, D.S. (SCHOOL SCIENCE, 2006)
Acharya Jagadish Chandra Bose occupies a high, almost unique, place in the recent history of Indian science. He was an investigator of uncommon courage, resourcefulness and dedication. Bose’s scientific work broadly falls under three periods. From 1894 to 1899 he was almost entirely concerned with the study of electric waves; between 1899 and 1902 he shifted from the physical to the biophysical field, and beyond 1903 he was occupied with the study of plant-responses under physical stimuli of various types. For these studies he developed and constructed his own instruments which were remarkable for their originality and extreme sensitivity.